Sample analyses for Vaccinium vitis-idaea bioactive compounds extraction - Yukhnenko, Maryna (Problems of Environmental Biotechnology, 2021)
The study of bioactive compounds content of V. vitis-idaea was carried out. Samples of V. vitis-idaea from two different regions of Ukraine were analyzed. All analyses were carried out according to standard methods. The standard procedure for the isolation and analysis of substances was based on extraction with the subsequent titration. The fulfilled analyses demonstrated that lingonberry material collected in Zakarpattia oblast has much better quality, with higher content of vitamin C and arbutin, and lower level of radioactivity.